STYLISTIC ANALYSIS USED BY EARNEST HEMINGWAY TO REVEAL THE INNER FEELING OF THE HERO 2020 - Thiab, Ahlam Abdulrazzaq (International Journal of Psychosocial Rehabilitation, 2020)
The topic of this study is “Stylistic Analysis used by Earnest Hemingway to reveal the inner feeling of the hero.” This study describes the stylistic analysis of the imageries and expressive means used in Earnest Hemingway’s novella “The Old Man and the Sea” to reveal the insides and the role of the hero. These devices along with the images and expressive means play a philosophical, sociological and psychological mirror of what is hidden inside the hero’s mind and psyche. That’s why it is important to analyze them to find out the essential roles of stylistic devices and to portray it as a characteristic device in narration and as a mirror, disclosing the spiritual, inner and psychological state of the hero. In our study we analyze several imageries and stylistic devices and highlight them with the help of synchronic approaches and various methods of investigation: critical analysis and synthesis of the literature, discourse analysis, biodata analysis, and cultural – historical analysis. In order to show the effective role of the hero, we analyze various images and stylistic devices that construct the plot and climax of the novella; make the componential analysis of the chosen quotations and present our own analysis of these quotations depending on both: the inner state of the author and the outsider situation; make observations concerning various themes and problems. In this project, we introduce all the images, which demonstrate various symbols in the hero’s life and in his hard society, which in turn characterize the individual style of the author. We expect this new analysis will significantly help all students who have interest in both fictional and non-fictional texts. We can also forecast that it will be extended to analyze other stylistic devices and imageries in diverse texts.